Akibat Hukum Pembatalan Perjanjian Pengikatan Jual Beli Oleh Pengadilan Karena Wanprestasi Tanpa Ganti Rugi - Muhamad Rizki; Jum Anggriani; Yoelianto (CV Rewang Rencang, 2025)
The Sale and Purchase Binding Agreement (PPJB) is an initial agreement before an official sale and purchase transaction takes place. One form of breach of contract in this agreement is the seller's failure to fulfill their obligations on time. This study discusses the legal consequences and protection for plantation landowners due to the cancellation of the PPJB by the court resulting from the buyer's breach. Furthermore, this study examines the court's legal considerations in declaring the buyer in breach without accounting for the seller’s losses, including damage to coconut trees on the land. This thesis uses a normative legal research method to analyze the legal consequences and protection for landowners whose PPJB was canceled by the court due to the buyer's breach. The cancellation of the agreement makes it legally void, meaning that the cancellation of the PPJB without compensation shows a lack of legal protection for the seller. According to Article 1267 of the Indonesian Civil Code, the cancellation of an agreement should restore the original condition and provide compensation to the landowner. This is in line with Articles 1243, 1244, and 1246 of the Civil Code, which state that a party in breach must be held accountable for the resulting damages. In case No. 160/Pdt.G/2021/PN Ktg, the judge was considered to have erred by rejecting the plaintiff’s compensation claim. Although the land and down payment were returned, the defendant was not required to compensate for the unauthorized use of the land. The judge should have considered the principle of restitutio in integrum, which means restoring the original condition, including compensation for the damaged coconut trees. By neglecting this, the judge's decision is seen as failing to reflect the principles of justice and legal certainty.